2010
DOI: 10.1111/j.1471-4159.2010.06841.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurr1 regulates RET expression in dopamine neurons of adult rat midbrain

Abstract: Genesis of midbrain dopamine (DA) neurons depends on Nurr1, a nuclear receptor expressed during development and adulthood in these neurons. Nurr1 is required for the expression of genes of dopaminergic phenotype such as tyrosine hydroxylase and DA transporter. The expression of the tyrosine kinase receptor RET also depends on Nurr1 during development. However, it is unknown whether RET expression is regulated by Nurr1 during adulthood, and the mechanism by which Nurr1 regulates RET expression. Using an adeno-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Myc-CoREST2-and Myc-CoREST3-expressing plasmids were generated by PCR from pEXPRESS and cloned into pCS2ϩMT. Myc-CoREST2 lacking the ELM2 domain, Myc-CoREST2 with the ELM2 of CoREST1, and CoREST2 containing point mutations were generated using previously described protocols (30). Mutants of CoREST2 were subcloned from pCS2ϩMT into pSG424 using standard cloning methods.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myc-CoREST2-and Myc-CoREST3-expressing plasmids were generated by PCR from pEXPRESS and cloned into pCS2ϩMT. Myc-CoREST2 lacking the ELM2 domain, Myc-CoREST2 with the ELM2 of CoREST1, and CoREST2 containing point mutations were generated using previously described protocols (30). Mutants of CoREST2 were subcloned from pCS2ϩMT into pSG424 using standard cloning methods.…”
Section: Animalsmentioning
confidence: 99%
“…Transient-transfection and reporter gene assays were performed as we described previously (30). We used the reporter plasmid G5S4tkLuc, which encodes firefly luciferase and is driven by a system containing 5 upstream activation sequences (UAS) and four elements for the SP1 transcriptional activator, upstream of the thymidine kinase promoter (0.102 g), at molar ratios of 1:1, 1:0.5, and 1:0.25 relative to Gal4-CoREST expression vectors.…”
Section: Animalsmentioning
confidence: 99%
“…Surprisingly, however, as discussed above, we found that a number of the known transcriptional targets of Nurr1, including Th, Dat, Vmat2, and Ret -the high affinity ligandbinding component of the Gdnf receptor complex (Baloh et al, 2000;Galleguillos et al, 2010), were not altered in SN DA neurons of old animals. In contrast, expression of Gch1, another target of Nurr1 (Gil et al, 2007), was significantly reduced.…”
Section: Discussionmentioning
confidence: 58%
“…Also indicated (in the center and right-hand columns) are NURR1-responsive genes seen in our profiling dataset that had been previously suggested as possible NURR1 targets based on more limited evidence (i.e., solely on differential expression in the Nurr1 knockout mouse or NURR1 ChIP-on-chip data; Table 1; Sacchetti et al, 1999, 2001; Iwawaki et al, 2000; Wallen et al, 2001; Hermanson et al, 2003, 2006; Lammi et al, 2004; Davies et al, 2005; Gil et al, 2007; Kitagawa et al, 2007; Luo et al, 2007; Sousa et al, 2007; Volpicelli et al, 2007; Yang and Latchman, 2008; Jacobs et al, 2009a; Galleguillos et al, 2010). The magnitude and directionality of NURR1-responsiveness we observed in these latter groups was the same as that seen for more well-documented NURR1 targets, providing confirmatory biological evidence in support of their inclusion as members of an expanded list of NURR1-responsive genes.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of genes regulated by NURR1 has come about largely by determining changes in midbrain gene expression occurring in the Nurr1 -null mouse or by acute over-expression of NURR1 in various cell lines (Sacchetti et al, 1999, 2001; Iwawaki et al, 2000; Wallen et al, 2001; Hermanson et al, 2003, 2006; Lammi et al, 2004; Davies et al, 2005; Gil et al, 2007; Kitagawa et al, 2007; Luo et al, 2007; Sousa et al, 2007; Volpicelli et al, 2007; Yang and Latchman, 2008; Jacobs et al, 2009a; Galleguillos et al, 2010). Surprisingly, there seems to be quite limited concordance among these datasets, exemplified by a recent study (Jacobs et al, 2009a) in which only one in eight genes differentially expressed in the Nurr1 -null midbrain was also affected by transient NURR1 over-expression in a mouse-derived cell model system (with many of the affected transcripts showing similar directionality of change after both the loss of NURR1 and NURR1 over-expression ).…”
Section: Introductionmentioning
confidence: 99%